Cassava soils and nutrient management in South Vietnam - Cong Doan Sat; Deturck, P. (International Center for Tropical Agriculture, 1998)
In South Vietnam, cassava is grown both in the highlands and in the delta, on different soil groups, such as the yellowish red soils, grey degraded soils, alluvial soils and acid sulfate soils. These soils are located mostly in the Central Highlands, the Coastal Region and the Eastern Region of South Vietnam, where perrenial crops such as coffee, tea and rubber are also grown. Cassava is often grown on unfertile soils. As a result, the soil becomes poorer and poorer leading to a decline in soil productivity.